Wednesday

November 26, 2014

November 26, 2014

Posted by **john** on Thursday, March 31, 2011 at 2:29pm.

- calculus -
**Reiny**, Thursday, March 31, 2011 at 2:33pmI don't know what name they give the rule these days, but the way I do it would get you ...

f'(x) = (3/2)(2x-6)(x^2 - 6x + 23)^(1/2) in one step.

and

= 3(x-3)√(x^2 - 6x + 23)

**Answer this Question**

**Related Questions**

math - can some one please help me with the following questions as i dont ...

calculus - I have been asked to solve this two different ways. The first way is...

Calculus - I'm having problems with this one. Can't get the right answer. ...

CALCULUS!! OH DEATH!!! - I need to solve: Lim as x is approaching 1/4, for (4x-1...

maths - differentiate the following function using the composite rule h(x)=e^x(4...

Calculus - I need help finding the derivative of this function: f(x)=(X^2+2)^4/5...

Math Analysis - Let f(x)= x^3, g(x) = sqrt x, h(x) = x-4, and j(x)= 2x. Express ...

Evolutionary Bio - How would you differentiate a monophyletic from a ...

Calculus - Find a formula for the derivatives of the function m(x)=1/(x+1) ...

calculus - Please help. Applying the chain rule, how do I find the derivative of...